Analysis of Prospects and Opportunities for Tour and Travel Business at CV Trans Cemerlang - Fitriana, Anissa Dian; Anas, Muhammad (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Along with the growth of the tourism industry and the rapid growth of the travel service provider business, tour, and travel companies such as CV Trans Cemerlang have an essential role in providing complete and organized travel services for tourists. However, despite having good prospects, businesses like CV Trans Cemerlang still face various obstacles related to operations and marketing. CV Trans Cemerlang is a company engaged in tour and travel services. This study aimed to analyze the opportunities and prospects of the tour and travel business at CV Trans Cemerlang. This research method is using a qualitative approach. Primary data was obtained through interviews with the owner of CV Trans Cemerlang and his team, then analyzed using SWOT analysis to determine business prospects and opportunities at CV Trans Cemerlang. The results of the SWOT analysis show that CV Trans Cemerlang has a profitable business opportunity for the long term. Several factors that need to be considered in running a business include negotiations with consumers, marketing services, and innovation to attract potential customers interested in tour and travel services from CV Trans Cemerlang.